1995
DOI: 10.1086/176281
|View full text |Cite
|
Sign up to set email alerts
|

Naked-Eye Observable Microlensing Events

Abstract: We study the naked-eye observability of microlensing events for both known stars and possible massive compact halo objects (MACHOs). We nd that if both the dark matter disc and halo are composed of MACHOs in the Jupiter-mass range, microlensing events of naked-eye stars, undergoing at least one magnitude of magni cation occur at the rate of 1 per 2400 years, and have durations of from hours to days; we may thus surmise that the chance of at least one event occurring in the era of recorded history (the last 5,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In support of this claim, the PLANCK collaboration [425] team published results stating that the polarized thermal emission from Galactic dust is the main foreground present in measurements of the polarization of the CMBR at frequencies above 100 GHz. Colley and Gott [426] analyzed the genus topology of the BICEP2 B-modes in the BICEP2 region from the publicly available Q and U at 353 GHz preliminary PLANCK polarization maps and concluded that they have a primordial origin. This debate is ongoing, but should be resolved once the additional data from the future Keck Array observations at 100 GHz and PLANCK observations at higher frequencies become available.…”
Section: Bicep2mentioning
confidence: 99%
“…In support of this claim, the PLANCK collaboration [425] team published results stating that the polarized thermal emission from Galactic dust is the main foreground present in measurements of the polarization of the CMBR at frequencies above 100 GHz. Colley and Gott [426] analyzed the genus topology of the BICEP2 B-modes in the BICEP2 region from the publicly available Q and U at 353 GHz preliminary PLANCK polarization maps and concluded that they have a primordial origin. This debate is ongoing, but should be resolved once the additional data from the future Keck Array observations at 100 GHz and PLANCK observations at higher frequencies become available.…”
Section: Bicep2mentioning
confidence: 99%
“…Recently, there have also appeared the progresses to ensure the BICEP2 statements in Ref. [32]. It is also remarked that the representation of α s is also given in Ref.…”
Section: Comparison With the Observationsmentioning
confidence: 99%
“…9 The tadpole condition is another important issue for implementing the KNP mechanism in the string theory, which requires a number of (brane) charges through the alignment of wrapping numbers of branes or gauge fluxes on branes in the extra dimensions, while the net charge of branes should be vanishing in the compact extra dimension. 10 In this respect, it is interesting to consider a possibility that the inflaton consists of RR two-form axions in type IIB model [42,44,45,47] and fluxed seven branes, which produce non-perturbative inflaton potential, are wrapping on a curved extra dimension with orientifolds. In this case, a tight consistency condition on three brane charges can be relaxed by the curvature corrections due to the seven branes [79,80].…”
Section: Discussionmentioning
confidence: 99%